Pengajaran dan Pendapatan Industri untuk Meningkatkan Pandangan Internasional pada Universitas-Universitas di Indonesia - Cliff Kohardinata; Luky Patricia Widianingsih (Journal on Education, 2023)
This study aims to provide empirical evidence on the influence of teaching, research, citation, and industry income variables on the international outlook of universities in Indonesia. The study uses a multiple linear regression approach, using data from the World University Ranking provided by The Times Higher Education. The sample consists of Indonesian universities listed in the World University Ranking during the period from 2019 to 2023. The results show a significant positive impact of teaching and industry income variables on the international outlook of universities. However, the study also reveals that research and citation variables do not have a significant impact on the international outlook of universities.